A comunicação do imaginário nas histórias em quadrinhos do Pato Donald: um estudo da linguagem de Carl Barks - Carvalho, André Campos de (2012)
Graphic expression and verbal narrative are the main constitutive elements of the language of comics, and its media features have been already studied by several authors: Juan Acevedo, Daniele Barbieri, Luiz Carneiro, Umberto Eco, Scott McCloud, Décio Pignatari, Paulo Ramos, and Waldomiro Vergueiro. This master s degree dissertation seeks to contribute to these studies conducting an investigation concerning the characterization of the myth of the self-made man, present in the American imaginary, through the analysis of narratives of American cartoonist Carl Barks, a major user of Comic Stories as a language in the twentieth century. This dissertation aims to understand the main criticism of Barks to the myth of the self-made man and the Success ethic in American culture of the twentieth century through a rapprochement with the studies of the imaginarium. We analyze the image of Donald Duck, specifically the plots portraying his attempts to be successful, and characteristics that guide these narratives. This hypothesis analyses the myth of self-made man and its incorporation into Western culture, and the confrontation of the concept of career success versus frustration in modern society, it is possible to find features that guide the cartoonist's graphic narratives. About Barks's work we relied on work done by Thomas Andrae, Michael Barrier and Geoffrey Blum. The theoretical basis for the field of communication focuses on the vision of Vilém Flusser. For studies of the imaginarium depart from the viewpoint of Gilbert Durand, who defines the imaginary as a reservoir of all images, narratives, values, perspectives, points of departure, cognitive processes, myths, legends, art, conceptual frameworks that interfere with the perception of the world and in building a culture. The theory of mith-hermeneutic extracted from the work of Marcos Ferreira dos Santos. The study of the language of comics is based on the work of Paulo Ramos. The research body is formed by the work of Carl Barks, published between 1942 and 1966, accessed by contemporary reissues, as well as interviews and commentary. The methodology involved literature review, observation and analysis of works from a diachronic perspective based on the readings of the imaginary, cultural studies and mith-hermeneutic. Conclusively, its creation, extensive studied body of work and republications indicate the persistence and resilience of the myth of self-made man in American culture